FMNH2-dependent monooxygenases initiate catabolism of sulfonamides in Microbacterium sp. strain BR1 subsisting on sulfonamide antibiotics - Ricken, Benjamin; Kolvenbach, Boris A; Bergesch, Christian; Benndorf, Dirk; Kroll, Kevin; Strnad, Hynek; Vlček, Čestmír; Adaixo, Ricardo; Hammes, Frederik; Shahgaldian, Patrick; Schäffer, Andreas; Kohler, Hans-Peter E; et al. (Scientific reports, 2017)
We report a cluster of genes encoding two monooxygenases (SadA and SadB) and one FMN reductase (SadC) that enable Microbacterium sp. strain BR1 and other Actinomycetes to inactivate sulfonamide antibiotics. Our results show that SadA and SadC are responsible for the initial attack of sulfonamide molecules resulting in the release of 4-aminophenol. The latter is further transformed into 1,2,4-trihydroxybenzene by SadB and SadC prior to mineralization and concomitant production of biomass. As the degradation products lack antibiotic activity, the presence of SadA will result in an alleviated bacteriostatic effect of sulfonamides. In addition to the relief from antibiotic stress this bacterium gains access to an additional carbon source when this gene cluster is expressed. As degradation of sulfonamides was also observed when Microbacterium sp. strain BR1 was grown on artificial urine medium, colonization with such strains may impede common sulfonamide treatment during co-infections with pathogens of the urinary tract. This case of biodegradation exemplifies the evolving catabolic capacity of bacteria, given that sulfonamide bacteriostatic are purely of synthetic origin. The wide distribution of this cluster in Actinomycetes and the presence of traA encoding a relaxase in its vicinity suggest that this cluster is mobile and that is rather alarming.
Keywords: Flavin Mononucleotide; biodegradace; flavinmononukleotid; multigenová rodina; bakteriální geny; radioizotopy uhlíku; Anti-Bacterial Agents; Sulfonamides; Mixed Function Oxygenases; Phylogeny; hydrochinony; Carbon Radioisotopes; sulfonamidy; Actinobacteria; Biodegradation, Environmental; Hydroquinones; Genes, Bacterial; antibakteriální látky; fylogeneze; oxygenasy se smíšenou funkcí; Multigene Family